GRIDSpace: semantic grid services on the web - evolution towards a softgrid - Dillon, Tharam S.; Wu, Chen; Chang, Elizabeth (IEEE, 2007)
This paper advances the notion of software in existing Grid services as discussed in OGSA, which provides software middleware or wrappers for accessing hardware resources towards the notion that the resources provided can be hardware, software, or hybrid hardware/software. It also proposes an approach using the integration of Grid service, Semantic Grid, and Web2.0 to overcome some of the limitations of the existing Web services architecture which relies on having the Web version of the RPCmechanism and thus has difficulty in dealing with massive scale of user participation and communication across the Internet. The new approach produces a novel Grid architecture GRIDSpace.